Kinematics and pushrim kinetics in adolescents propelling high-strength lightweight and ultra-lightweight manual wheelchairs. (3rd April 2019) - Oliveira, Nuno; Blochlinger, Sheila; Ehrenberg, Naphtaly; Defosse, Theresa; Forrest, Gail; Dyson-Hudson, Trevor; Barrance, Peter
Abstract: Purpose: The purpose of this study is to describe and compare pushrim forces, propulsive work cost, and upper body kinematics in adolescents propelling (1) a standard high strength lightweight wheelchair, and (2) an ultra-lightweight wheelchair with adjustable main axle positioning, on a level tiled floor ("Tile"), ascending a ramp ("Ramp"), and across a foam mat ("Mat"). Methods: A within-subjects repeated measures study design was used. Eight adolescent manual wheelchair users propelled the standard and ultra-lightweight wheelchairs across the three conditions. Average pushrim tangential force, propulsive power and work per unit distance travelled, as well as upper body kinematic angles, were analyzed. Results: Average pushrim tangential force (1.80 ± 0.7 N, p  = .042) and propulsive work per unit distance travelled (8.3 ± 1.7 J·m − 1, p  = .002) were higher for the standard lightweight wheelchair, whereas average speed was lower (0.12 ± 0.03 m/s, p  = .006). Maximum shoulder (9.2 ± 2.0°, p  = .003) and elbow flexion (8.0 ± 2.2°, p  = .009) were higher for the ultra-lightweight wheelchair. Compared with Tile, propulsion on Mat and Ramp was associated with higher average tangential force, work per unit distance, power, and maximum flexion of the neck and trunk, whereas shoulder extension and average speed were lower for Mat and Ramp. Conclusions: Compared with the standard lightweight wheelchair, ultra-lightweight wheelchair propulsion was associated with lower pushrim forces, lower energy costs, higher self-selected speeds, and increased shoulder and elbow flexion. These variables have been linked to injury risk and mobility efficiency, and the results provided evidence that differences in weight and configuration options are both contributors. Findings can inform decision-making in the prescription of manual wheelchairs for pre-adult populations. Implications for Rehabilitation: A significant proportion of manual wheelchair users are children and adolescents, and due to the early onset of use they may be especially predisposed to the development of chronic overuse injuries. The study reports differences in energy costs, pushrim forces, and upper body kinematics measured when adolescents propelled standard and ultra-lightweight wheelchairs across three trial conditions. In the ultra-lightweight wheelchair, reduced energy cost is linked to more efficient mobility, and lower forces may be linked to lower risk of chronic injury. Significant differences in elbow and shoulder kinematics are also reported, and the findings support the importance of both weight and setup options in the selection of manual wheelchairs.